Generation of ultrahigh fields by microbubble implosion - M. Murakami; A. Arefiev; M. A. Zosa; J. Honrubia (Physical Sciences and Technology, 2019)
Breaking the 100-MeV barrier for proton acceleration will help elucidate fundamental physics and advance practical applications from inertial confinement fusion to tumor therapy. A novel concept of “microbubble implosion (MBI)” is proposed. In the MBI concept, bubble implosion combines micro-bubbles and ultraintense laser pulses of 1020 – 1022 Wcm-2 to generate ultrahigh fields and relativistic protons. The bubble wall protons are subject to volumetric acceleration toward the center due to the spherically symmetric electrostatic force generated by hot electrons filling the bubble. Such an implosion can generate an ultrahigh density proton core of nanometer size on the collapse, which results in an ultrahigh electrostatic field to emit energetic protons in the relativistic regime. Laser intensity scaling is investigated for accelerated proton energy and attainable electrostatic field using MBI. Three-dimensional particle-in-cell and molecular dynamics simulations are conducted in a complementary manner. As a result, underlying physics of MBI are revealed such as bubble-pulsation and ultrahigh energy densities, which are higher by orders of magnitude than, for example, those expected in a fusion-igniting core of inertially confined plasma. MBI has potential as a plasma-optical device, which optimally amplifies an applied laser intensity by a factor of two orders of magnitude; thus, MBI is proposed to be a novel approach to the Schwinger limit.